Factors controlling spatial distribution of complex lithology in transitional shale strata: Implications from logging and 3D seismic data, Shan-2 Lower Sub-member, Eastern Ordos Basin - Wang, Xuxu; Zhou, Lu; Wu, Yong; Li, Shuxin; Gu, Yifan; Li, Xingtao (Frontiers in Earth Science, 2023)
The Shanxi Formation Shan-2 Lower Sub-member transitional shale in the eastern Ordos Basin is characterized by high total organic carbon value, wide distribution, and large single-layer/cumulative thickness; it is the key target interval for transitional shale gas exploration. Based on drilling, logging, 3D seismic, and natural energy spectrum data, this study discusses the spatial distribution and controlling factors of complex lithology in the transitional shale stratum. Using the multi-lithological eigenvalue method, the lithologic differential distribution characteristics of the Shan-2 Lower Sub-member were identified through seismic attribute analysis and post-stack seismic parameter inversion. On this basis, the controlling factors of lithology spatial difference distribution are revealed by paleogeomorphology restoration, the sedimentary environmental indicator characteristics of shale, and seismic facies division. The results indicate that the lithology distribution of transitional shale strata in the Shan-2 Lower Sub-member is significantly different, and the geomorphological pattern of interjacent depressions and highlands lays a foundation for the formation of the sedimentary system. The environmental and energy differences of paleo-sedimentary water form a sedimentary environment with frequent facies transitions, which controls the distribution of sediments. Th/U and Th/K radios, which indicate redox conditions and sedimentary water energy during the early sedimentary stage of the Shan-2 Lower Sub-member, show that the geomorphic uplift area is characterized by a high-energy transitional environment of mainly developed sandstone and silty mudstone, while the depression is relatively low-energy under a brackish water reduction environment, mainly composed of both dark and carbonaceous shale. During the late sedimentary stage of the Shan-2 Lower Sub-member, when geomorphic control was weakened, it presented a shallow-water, high-energy, and oxidized transitional environment, with a lithology dominated by the complex interbedding of fine-grained sandstone, silty shale, shale, carbonaceous shale, and coal seam. Therefore, it is inferred that the Shan-2 Lower Sub-member may have developed as a barrier island-lagoon sedimentary model. The early depositional period was dominated by barrier island-lagoon-tidal flat depositional combination, thence the sedimentary environment gradually evolved into a tidal flat-swamp environment.